Benchmarking knowledge, attitudes and practices on food allergies and celiac disease among food service staff: exploratory findings and policy gaps - Figueroa-Gómez, Ximena; Rodríguez, Juan Manuel; Oliveras-López, María-Jesús; Poyanco, Marcelo; López, Herminia; Martínez-Martínez, Fernando; Araya, Magdalena (Frontiers in Nutrition, 2025)
This exploratory study examines how foodservice workers in Chile manage the dietary needs of individuals with food allergies (FA) and celiac disease (CD), presenting Chile as a case study that, despite its formal classification as a high-income country, shares regulatory and operational gaps with emerging economies in transition. A cross-sectional survey of 397 restaurant and foodservice employees in Santiago evaluated their knowledge, attitudes, and practices (KAP) regarding FA and CD. Simultaneously, a structured narrative review of 26 international studies published between 2010 and 2024 was conducted to benchmark national findings against global trends. Results revealed that 87.5% of participants had never received formal training, and less than 2% achieved acceptable performance, defined as ≥50% correct responses across all KAP dimensions. Statistically significant associations were found between higher KAP scores and factors such as education level, managerial position, and length of professional experience. Conversely, foreign-born workers and those in fast-food settings showed lower performance, exposing structural vulnerabilities. The international comparison underscored widespread deficiencies even in countries with allergen regulations, highlighting that legislation alone is insufficient without mandatory training and enforcement. These findings highlight serious risks and support a phased national strategy, beginning with pilot interventions, rather than immediate policy change. This study also offers a replicable methodology for assessing and improving allergen safety in foodservice environments across emerging economies.